PENGARUH SUHU EKSTRAKSI TERHADAP KANDUNGAN TOTAL FENOL PADA TETES TEBU: The Effect Of Temperature Extraction On Total Phenol Content In Sugar Cane Moss - Pamungkas, Pinctada Putri; Khurniyati, Maylina Ilhami; M. Khusaeri; Julaikha, Siti (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2024)
Molasses is a by-product of the sugar processing industry that still contains sugar and organic acids. Molasses produced by the sugar cane industry in Indonesia is known by another name, namely Molasses. The sucrose content in molasses is quite high, ranging from 48-55%. Phenolic compounds are compounds produced by plants in response to environmental stress. The components in this compound are believed to have an important role as agents for preventing and treating disorders such as arteriosclerosis, brain dysfunction, diabetes and cancer. The method used in this study is a qualitative method, namely the Sonication extraction treatment using temperature variations. The total phenolic compound content in S2 drops with a temperature treatment of 50ºC got the best results, namely 0.23%. While the lowest value was found in the S3 treatment with a temperature of 60ºC of 0.19%. The greater the total phenolic value in the molasses extract, the greater the compound content in it. concentration 0.23%.